A Inherent Occupational Health Assessment for Alternative Hydrogen Synthesis Pathways (Journal of Energy and Safety Technology (JEST), 2023)
Hydrogen is one of the most investigated topics in energy transition due to its sustainability and vast applicability. However, it has health and safety challenges like any other chemical process. Most attention focuses on this fuel production's technology and economic potential with some work related to its safety impact. This study conducts an occupational health hazard assessment on two hydrogen synthesis routes at the design research and development stage. This study compares the outcomes to find the healthiest Hydrogen production route. This research leveraged the Inherent Occupational Health Index (IOHI) as the assessment to measure the health challenges peculiar to each production route. Three different index calculation types additive, average, and worst case are used to achieve the comparison. The information used in the evaluation is available at the R&D design stage. The study shows that both synthesis routes assessed steam methane reforming and coal gasification fall under the hazardous category of the IOHI index standard. But steam methane reforming has a lower IOHI index standard value of 16 than coal gasification 17.7. Therefore, although both synthesis routes are hazardous and pose occupational health risks to workers, steam methane reforming is a better alternative for hydrogen production from a health perspective.
Keywords: Inherent Health; Health Hazard; Research and Development; Hydrogen Synthesis; Worker’s Health